Panax Ginseng C.A.Mey. as Medicine: The Potential Use of Panax Ginseng C.A.Mey. as a Remedy for Kidney Protection from a Pharmacological Perspective - Jin, De; Zhang, Yuqin; Zhang, Yuehong; Duan, Liyun; Zhou, Rongrong; Duan, Yingyin; Sun, Yuting; Lian, Fengmei; Tong, Xiaolin (Frontiers in Pharmacology, 2021)
Panax ginseng C.A.Mey. has been widely consumed as food/diet supplements from natural sources, and its therapeutic properties have also aroused widespread concern. Therapeutic properties of Panax ginseng C.A.Mey. such as anti-inflammatory, ameliorating chronic inflammation, enhancing the immunity, resisting the oxidation again, and regulating the glucose and lipid metabolism have been widely reported. Recent years, lots of interesting studies have reported the potential use of Panax ginseng C.A.Mey. in the management of DKD. DKD has become the leading cause of end-stage renal disease worldwide, which increases the risk of premature death and poses a serious financial burden. Although DKD is somehow controllable with different drugs such as Angiotensin-Converting Enzyme Inhibitors (ACEI), Angiotensin Receptor Blockers (ARB) and lowering-glucose agents, modern dietary changes associated with DKD have facilitated research to assess the preventive and therapeutic merits of diet supplements from natural sources as medicine including Panax ginseng C.A.Mey. Findings from many scientific evidences have suggested that Panax ginseng C.A.Mey. can relieve the pathological status in cellular and animal models of DKD. Moreover, a few studies showed that alleviation of clinical phenotype such as reducing albuminuria, serum creatinine and renal anemia in DKD patients after application or consumption of Panax ginseng C.A.Mey.. Therefore, this review aims to discuss the effectiveness of Panax ginseng C.A.Mey. as medicine for targeting pathological phenotypes in DKD from a pharmacological perspective. This review will provide new insights into the potential understanding use of Panax ginseng C.A.Mey. in the management of DKD in clinical settings.